The Crust in the Pamir: Insights From Receiver Functions. Issue 8 (22nd August 2019) - Schneider, F.M.; Yuan, X.; Schurr, B.; Mechie, J.; Sippl, C.; Kufner, S.‐K.; Ratschbacher, L.; Tilmann, F.; Oimahmadov, I.; Gadoev, M.; Minaev, V.; Abdybachaev, U.; et al.
Abstract: The Cenozoic convergence between India and Asia has created Earth's thickest crust in the Pamir‐Tibet Plateau by extreme crustal shortening. Here we study the crustal structure of the Pamir and western Tian Shan, the adjacent margins of the Tajik, Tarim, and Ferghana Basins, and the Hindu Kush, using data collected by temporary seismic experiments. We derive, compare, and combine independent observations from P and S receiver functions. The obtained Moho depth varies from ~40 km below the basins to a double‐normal thickness of 65–75 km underneath the Pamir and Hindu Kush. A Moho doublet—with the deeper interface down to a depth of ~90 km—coincides with the arc of intermediate‐depth seismicity underneath the Pamir, where Asian continental lower crust delaminates and rolls back. The crust beneath most of the Central and South Pamir has a low V p / V s ratio (<1.70), suggesting a dominantly felsic composition, probably a result of delamination/foundering of the mafic rocks of the lower crust. Beneath the Cenozoic gneiss domes of the Central and South Pamir, which represent extensional core complexes, the V p / V s ratios are moderate to high (~1.75), consistent with the previously observed, midcrustal low‐velocity zones, implying the presence of crustal partial melts. Even higher crustal average V p / V s ratios up to 1.90 are found in the sedimentary basins and along the Main Pamir Thrust. The ratios along the latter—the active thrust front of the Pamir—may reflect fluid accumulations within a strongly fractured fault system. Key Points: Double normal crustal thickness of 65–75 km underneath the Pamir and Hindu Kush transitions to ~40 km below the surrounding basins Double Moho beneath the Central and western South Pamir indicates that Tajik/Tarim continental crust underlies Pamir crust Low V p / V s in South and Central Pamir crust suggests bulk felsic composition due to delamination/foundering of the mafic lower crust